RENOVASI POLA PIKIR IMPLEMENTASI CSR MENUJU METAMORFOSIS PEREKONOMIAN INDONESIA - Dermawan, Elizabeth Sugiarto (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2010)
The way of thinking Corporate Social Responsibility (CSR) implementation in Indonesia should be renovated to make a better change for the economic growth. Most of CSR activities is just a charity and often seen as a burden that impedes the company growth, and may impact on the growth of Indonesian economy. As reported in CSR Indonesia Newsletter vol.3 (2009) under Indonesian law, private companies are obliged to carry out CSR programs and State-owned companies are also bound by law to carry out CSR programs known as Partnership Program and Community Development (PKLB) although that is a good policy but most companies currentlyÂ view CSR as an obligation rather than a responsibility. Based on that reality, this article try to re-motivated especially the reader and in general for people in this country who become a stakeholders of a company have to be realized that this is the time to change the bad image of CSR. Stakeholdersâ€™ perception is the area of positioning the company image and this is an important part of business sustainability.